2015
DOI: 10.1162/jocn_a_00824
|View full text |Cite
|
Sign up to set email alerts
|

As Working Memory Grows: A Developmental Account of Neural Bases of Working Memory Capacity in 5- to 8-Year Old Children and Adults

Abstract: Working memory develops slowly: Even by age 8, children are able to maintain only half the number of items that adults can remember. Neural substrates that support performance on working memory tasks also have a slow developmental trajectory and typically activate to a lesser extent in children, relative to adults. Little is known about why younger participants elicit less neural activation. This may be due to maturational differences, differences in behavioral performance, or both. Here we investigate the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 66 publications
4
30
0
Order By: Relevance
“…This need has been identified, 90 but it is rare to see parametric protocols in developmental neuroscience. 91,92 In constructivist cognitive development, behavioural quantitative measures of mental attention, with scaled levels of effective complexity, have been used for years. They assess cognitive limitations as a function of age.…”
Section: Two Sorts Of Constructivist Developmental (Neo-piagetian) Thmentioning
confidence: 99%
“…This need has been identified, 90 but it is rare to see parametric protocols in developmental neuroscience. 91,92 In constructivist cognitive development, behavioural quantitative measures of mental attention, with scaled levels of effective complexity, have been used for years. They assess cognitive limitations as a function of age.…”
Section: Two Sorts Of Constructivist Developmental (Neo-piagetian) Thmentioning
confidence: 99%
“…Results have shown increasing capacity estimates from early childhood through adolescence (Buss, Fox, Boas, & Spencer, 2013; Cowan et al, 2005; Isbell, Fukuda, Neville, & Vogel, 2015; Kharitonova, Winter, & Sheridan, 2015; Riggs, McTaggart, Simpson, & Freeman, 2006; Riggs, Simpson, & Potts, 2011; Simmering, 2012; Simmering et al, 2015; see Simmering, in press, for discussion of paradigms used to estimate capacity during infancy), although the magnitudes and trajectories of these estimates varies widely across paradigms (see Simmering & Perone, 2013, for related discussion). Most developmental studies have either implicitly or explicitly endorsed a slot-like view, suggesting that the number of items that can be represented increases without addressing whether there are corresponding changes in resolution (e.g., Cowan et al, 2005; Isbell et al, 2015; Kharitonova et al, 2015; Riggs et al, 2006, 2011). …”
Section: Developmental Changes In Visual Working Memorymentioning
confidence: 99%
“…As noted above, most theories of development have focused on only one characteristic of VWM representations (e.g., capacity, Cowan et al, 2005; Isbell et al, 2015; Kharitonova et al, 2015; Riggs et al, 2006, 2011; or precision, Burnett Heyes et al, 2012) and have not considered how changes in one characteristic might impact performance across behavioral tasks. For example, although Burnett Heyes et al showed that precision improved developmentally when estimating the orientation of a bar held in memory alone or with two other items, they did not discuss how these changes in precision would affect performance in the change detection task used to estimate capacity.…”
Section: Developmental Changes In Visual Working Memorymentioning
confidence: 99%
“…The neural pathways outlined above are also likely to play a key role in shaping cognitive development in children exposed to deprived early environments. Reductions in cortical volume and thickness are likely to yield deficits in higher order cognitive functions such as EF, which requires coordinated function of multiple areas of association cortex, most notably late-developing areas of the brain such as the prefrontal and superior parietal cortices (D’Esposito et al, 1995; Finn et al, 2016; Finn, Sheridan, Kam, Hinshaw, & D’Esposito, 2010; Kharitonova, Winter, & Sheridan, 2015; Nomura et al, 2010; Peverill, McLaughlin, Finn, & Sheridan, 2016). Together, atypical neural and cognitive development among children exposed to early deprivation are associated with later risk for externalizing psychopathology (Machlin et al, 2017; McLaughlin et al, 2013; Tibu et al, 2015).…”
mentioning
confidence: 99%